A mathematical model of movement in virtual reality through thoughts - Ivan Trenchev; Radoslav Mavrevski; Metodi Traykov; Ilire Zajmi–Rugova (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this article, we'll introduce ways to build virtual worlds through different computer programs. We will show the method of rectangles for analyzing data obtained from the electroencephalogram. We will demonstrate basic mathematical models for movement prediction in a system of virtual reality. Using this data, the main transformations are possible-change of position and rotation (change of orientation).